2012
DOI: 10.1084/jem.20111703
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-induced IL-1β, but not IL-6, is critical for the development of steady-state TH17 cells in the intestine

Abstract: Homeostatic TH17 differentiation in the intestine is regulated by IL-1β secretion from intestinal macrophages stimulated by commensal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
277
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(305 citation statements)
references
References 24 publications
22
277
0
2
Order By: Relevance
“…IL-1b was linked to the promotion of Th17 development in models of autoimmune diseases and bacterial and fungal infections, as well as in inflammatory and steady-state conditions in the intestine (2,3,54,55). In line with this, we show in this study that IFN-g-induced suppression of IL-1b resulted in impaired generation of IL-17-producing cells in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…IL-1b was linked to the promotion of Th17 development in models of autoimmune diseases and bacterial and fungal infections, as well as in inflammatory and steady-state conditions in the intestine (2,3,54,55). In line with this, we show in this study that IFN-g-induced suppression of IL-1b resulted in impaired generation of IL-17-producing cells in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…Although these results support early in vitro studies (2-4) and one study showing that TGF-β1 was required for the initiation of EAE (14), they are in contrast to in vivo studies that showed that IL-6 is not required for microbiota-induced Th17 cell formation (9) and that TGF-β1 is not required for Th17 differentiation during EAE induction (8). The fact that IL-1β or IL-23 was important for Th17 cell differentiation in the cases where IL-6 or TGF-β1 was not suggests the existence of several independent Th17 cell differentiation pathways (8,9). The IL-6-and TGF-β1-dependent pathway induced by i.n.…”
Section: Discussionsupporting
confidence: 75%
“…infection by Streptococcus pyogenes, and TGF-β1 receptor signaling and IL-6 are involved (6,7). However, Th17 cell formation in the small intestine does not depend on TGF-β1 (8) and requires IL-1β but not IL-6 (9). Additionally, Kuchroo and colleagues reported that although Th17 differentiation was normally dependent on IL-6, it could occur without it through an IL-21-dependent pathway if regulatory T cells were absent (10).…”
mentioning
confidence: 99%
“…For example, IL-1b increases the cell response to anti-CD3 stimulation and encourages maturation toward IL-17A production in CD161 + T cells (25). Similarly, conventional CD4 + T cells with a Th17 signature possess extended functional plasticity, and IL-7 (29,30) or a combination of IL-1b and IL-23 (31,32) may reduce the T cell-activation threshold and positively influence differentiation toward Th17 cells. Because Liv-MAIT cells produced high quantities of IL-17A only after mitogen stimulation, we tested whether inflammatory cytokines influence the maturation and responsiveness of Liv-MAIT cells to TCR-mediated stimulation.…”
Section: Il-7 Licenses Mait Cells To Produce Large Quantities Of Ifn-mentioning
confidence: 99%